Kesadaran Beragama Pada Anak - Abdurahman, M.Pd, Abdurrahman (Institut Agama Islam Negeri Padangsidimpuan, 2019)
In a certain period humans are eager to escape from limited intentions to reach the core of the intent. In humans there is an urge and desire that will not be settled, calm and peaceful unless it has been related to this source of intent, namely God. This refers to the word of God,